Can We Predict Length of Stay for CJR Patients Who Sustain a Displaced Femoral Neck Fracture? - Meltzer-Bruhn, Ariana T.; Esper, Garrett W.; Ganta, Abhishek; Konda, Sanjit R.; Egol, Kenneth A. (The Journal of Hip Surgery, 2023)
The Comprehensive Care for Joint Replacement (CJR) model holds hospitals financially accountable for the outcomes of patients undergoing hip and knee replacements. The purpose of this study is to see if a validated inpatient risk assessment tool can be used to predict patients with poor outcomes following hip arthroplasty. We hypothesize that the validated risk prediction tool (Score for Trauma Triage in the Geriatric and Middle-Aged [STTGMA]) can be modeled to stratify these patients at highest risk for poor outcomes at emergency department (ED) presentation. Between October 2018 and September 2020, 237 patients subject to the CJR bundle program were treated for a displaced femoral neck fracture with total hip arthroplasty or hemiarthroplasty and analyzed for demographics, comorbidities, injury details, and outcomes. A poor outcome was considered to be a longer length of inpatient hospital stay, venous thromboembolism (VTE), or readmission within 30, 60, or 90 days. Each patient's STTGMA score was calculated using their demographics, functional status, and injury details at time of ED admission. Patients were divided into risk quartiles based on STTGMA score. The top 25% risk cohort was compared against the bottom 25% risk cohort using chi-square or t-tests as appropriate. Mean STGGMA scores were 0.046 ± 0.028 in the highest risk cohort and 0.007 ± 0.001 in the lowest risk cohort. STTGMA was able to adequately risk stratify patients at risk for a longer length of inpatient hospital stay (p < 0.01). The STTGMA tool was unable to risk stratify patients with postoperative VTE within 90 days (p = 0.986) or readmission within 90 days (p = 0.087). Providers can calculate STTGMA scores on admission for CJR patients to help identify which patients may require a longer length of inpatient hospital stay. These patients can be targeted with strategies to address these deficiencies.
Keywords: femoral neck fracture; bundled care model; risk assessment; hip arthroplasty